Exploring the pathological mechanisms underlying Cohen syndrome - Vacca, Fabrizio; Yalcin, Binnaz; Ansar, Muhammad (Frontiers in Neuroscience, 2024)
Cohen Syndrome (CS) is a rare autosomal recessive disorder caused by biallelic mutations in the VPS13B gene. It is characterized by multiple clinical features, including acquired microcephaly, developmental delay, intellectual disability, neutropenia, and retinal degeneration. VPS13B is part of the bridge-like lipid transport (BLTP) protein family, which in mammals also includes the VPS13A, -C and -D. The proteins of this family are peripheral membrane proteins with different sub-cellular localization, but all share similar structural features and have been proposed to act as lipid transport proteins at organellar membrane contact sites. VPS13B is localized at the Golgi apparatus and is essential for the maintenance of organelle architecture. Here we present a review of the experimental data on the function of the protein at the cellular level, discussing the potential link with disease phenotype and review the studies on animal models recapitulating features of the human disease.